Nitrogen Mineralization in Soil Amended with Crop Residue: An Incubation Experiment Under Flooding Conditions - K. Vimlesh; A. K. Giri (E-Journal of Chemistry)
Incubation studies were carried out to investigate the release of nitrogen in soils. The domestic sewage and soil were analyzed for their physical, chemical characteristics in view of evaluating their suitability for irrigation to agricultural lands in a laboratory experiment. The effluents were added to a soil and incubated at 30±1 0C microbial population, NH4+-N and NO3--N concentration were determined for 0,15,30,60 and 90 days. The purpose of this study was to determine nitrogen mineralization of domestic sludge in soils comparing leached and non leached incubation procedures